Islam and harm reduction - Kamarulzaman, A.; Saifuddeen, S.M. (Elsevier, 2010)
Although drugs are haram and therefore prohibited in Islam, illicit drug use is widespread in many Islamic countries throughout the world. In the last several years increased prevalence of this problem has been observed in many of these countries which has in turn led to increasing injecting drug use driven HIV/AIDS epidemic across the Islamic world. Whilst some countries have recently responded to the threat through the implementation of harm reduction programmes, many others have been slow to respond. In Islam, The Quran and the Prophetic traditions or the Sunnah are the central sources of references for the laws and principles that guide the Muslims' way of life and by which policies and guidelines for responses including that of contemporary social and health problems can be derived. The preservation and protection of the dignity of man, and steering mankind away from harm and destruction are central to the teachings of Islam. When viewed through the Islamic principles of the preservation and protection of the faith, life, intellect, progeny and wealth, harm reduction programmes are permissible and in fact provide a practical solution to a problem that could result in far greater damage to the society at large if left unaddressed. (C) 2009 Elsevier B.V. All rights reserved.